2021
DOI: 10.5195/jmla.2021.1135
|View full text |Cite
|
Sign up to set email alerts
|

Tableau (version 2020.3)

Abstract: This review analyzes the new features in Tableau and how it can be used both by librarians and the patrons they serve.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 4 publications
0
13
0
Order By: Relevance
“…The pre-survey and post-survey responses to each question were counted and collected into groups based on response type, then displayed using Tableau Software (Beard & Aghassibake, 2021). All de-identified audio recordings were stored in one folder containing their 4-digit codes without any indication of being from the pre-recordings or the post-recordings to help eliminate bias that could arise since student attempts in the post-recordings may be perceived as more proficient.…”
Section: Discussionmentioning
confidence: 99%
“…The pre-survey and post-survey responses to each question were counted and collected into groups based on response type, then displayed using Tableau Software (Beard & Aghassibake, 2021). All de-identified audio recordings were stored in one folder containing their 4-digit codes without any indication of being from the pre-recordings or the post-recordings to help eliminate bias that could arise since student attempts in the post-recordings may be perceived as more proficient.…”
Section: Discussionmentioning
confidence: 99%
“…Our choice to focus on REST API implementation instead of classical graphical user interface implementation is primarily motivated by a desire to give users a free choice to construct search requests whether they are simple or complex without limitations of standard use-cases that are typical for the latter. This approach allows the use of tools for data analysis [19], including the tools for building summary charts, which have recently become more and more widely used.…”
Section: Database Contentmentioning
confidence: 99%
“…Users can vote for questions and answers, both upvotes (positive feedback) and down votes (negative feedback) are allowed. The number of the upvotes minus the number of downvotes represent the score.It is the largest Software development Q&A community, according to the SO Annual developer survey 2019 8 which reported that SO had 80 million visit, of which 25% are developer professionals and university students, and more than 80% rely on SO for educational purposes and also 65% of Stack Overflow's professional developers contribute to open source projects.…”
Section: A Stack Overflow and Its Tagging Systemmentioning
confidence: 99%
“…To apply the approach and analyze data, we turned to the most useful and popular library for machine learning in Python Scikit-learn [7] and the full-featured AI and ML integrated tool that supports multiple scripting languages and is easy to work with huge datasets Tableau [8]. Scikit-learn ML is a high-level API built on data frames and datasets that allows pipelines and is easier to build.…”
Section: Introductionmentioning
confidence: 99%